2010
DOI: 10.1111/j.1600-0609.2010.01524.x
|View full text |Cite
|
Sign up to set email alerts
|

Addition of thalidomide to oral melphalan/prednisone in patients with multiple myeloma not eligible for transplantation: results of a randomized trial from the Turkish Myeloma Study Group

Abstract: The combination of melphalan-prednisone-thalidomide (MPT) has been investigated in several clinical studies that differed significantly with regard to patient characteristics and treatment schedules. This prospective trial differs from previous melphalan-prednisone (MP) vs. MPT trials by treatment dosing, duration, routine anticoagulation, and permission for a crossover. Newly diagnosed patients with multiple myeloma (MM) (n=122) aged greater than 55 yr, not eligible for transplantation were randomized to rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(91 citation statements)
references
References 10 publications
1
90
0
Order By: Relevance
“…Six randomized studies have compared MPT with melphalan, prednisone (MP) [70][71][72][73][74][75]. An OS advantage has been observed in three trials [70,71,74].…”
Section: Options For Initial Treatment In Patients Not Eligible For Asctmentioning
confidence: 99%
“…Six randomized studies have compared MPT with melphalan, prednisone (MP) [70][71][72][73][74][75]. An OS advantage has been observed in three trials [70,71,74].…”
Section: Options For Initial Treatment In Patients Not Eligible For Asctmentioning
confidence: 99%
“…35 In two other trials performed by the Nordic and Turkish groups, ORR was higher in patients who were given thalidomide, but this advantage did not translate into longer PFS and OS in comparison with those who did not receive thalidomide. [36] and [37] An efficacy meta-analysis of the six MPT trials including 1685 patients was conducted ( Table 2). 15 Despite the heterogeneity of the trials, both for patient characteristics and thalidomide schedules (dose and duration of treatment), the addition of thalidomide to MP significantly prolonged both PFS and extended OS by 20% (6.6 months) compared to MP.…”
Section: Imids-based Regimensmentioning
confidence: 99%
“…8 In the IFM01-01 study, conducted in 232 very elderly patients (aged 475 years), median OS was significantly longer in patients treated with MPT compared with MP alone (44.0 versus 29.1 months; HR ¼ 0.68; P ¼ 0.028). 9 A borderline significant improvement in OS for MPT versus MP was also reported by the Dutch-Belgium HematoOncology Cooperative Group in the HOVON-49 study ( 15 ) failed to show a persistent survival advantage with MPT. A meta-analysis of the six randomized trials of MPT versus MP (three of which included thalidomide maintenance therapy) has identified that the addition of thalidomide to MP as a frontline regimen in elderly NDMM patients significantly prolongs both PFS and OS by around 6 months compared with MP.…”
Section: Options Of Treatment As Induction Therapymentioning
confidence: 77%